Induction, isolation, and characterization of two laccases from the white rot basidiomycete Coriolopsis rigida - Saparrat, Mario Carlos Nazareno (2002)
Previous work has shown that the white rot fungus Coriolopsis rigida degraded wheat straw lignin and both the aliphatic and aromatic fractions of crude oil from contaminated soils. To better understand these processes, we studied the enzymatic composition of the ligninolytic system of this fungus. Since laccase was the sole ligninolytic enzyme found, we paid attention to the oxidative capabilities of this enzyme that would allow its participation in the mentioned degradative processes. We purified two laccase isoenzymes to electrophoretic homogeneity from copper-induced cultures. Both enzymes are monomeric proteins, with the same molecular mass (66 kDa), isoelectric point (3.9), N-linked carbohydrate content (9%), pH optima of 3.0 on 2,6-dimethoxyphenol (DMP) and 2.5 on 2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), absorption spectrum, and N-terminal amino acid sequence. They oxidized 4-anisidine and numerous phenolic compounds, including methoxyphenols, hydroquinones, and lignin-derived aldehydes and acids. Phenol red, an unusual substrate of laccase due to its high redox potential, was also oxidized. The highest enzyme affinity and efficiency were obtained with ABTS and, among phenolic compounds, with 2,6-dimethoxyhydroquinone (DBQH2). The presence of ABTS in the laccase reaction expanded the substrate range of C. rigida laccases to nonphenolic compounds and that of MBQH2 extended the reactions catalyzed by these enzymes to the production of H2O2, the oxidation of Mn2+, the reduction of Fe3+, and the generation of hydroxyl radicals. These results confirm the participation of laccase in the production of oxygen free radicals, suggesting novel uses of this enzyme in degradative processes.